How to Reach the Best Ultrasound Performance in the Delivery Room - Eduardo Félix Martins Santana; Renata Gomes Castello; Maria Eduarda Tenório Passos; Gabriela Carneiro Freitas Ribeiro; Edward Araujo Júnior (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2023)
Abstract Ultrasonography is an instrument that is present in the maternal-fetal assessment throughout pregnancy and with widely documented benefits, but its use in intrapartum is becoming increasingly relevant. From the assessment of labor progression to the assessment of placental disorders, ultrasound can be used to correlate with physiological findings and physical examination, as its benefit in the delivery room cannot yet be proven. There are still few professionals with adequate training for its use in the delivery room and for the correct interpretation of data. Thus, this article aims to present a review of the entire applicability of ultrasound in the delivery room, considering the main stages of labor. There is still limited research in evidence-based medicine of its various possible uses in intrapartum, but it is expected that further studies can bring improvements in the quality of maternal and neonatal health during labor.